Effect of a low-dose interventional x-ray system on radiation exposure in the higher body surface area patient population. Issue 4 (2nd October 2018) - Memon, Sehrish; Larsen, Timothy R.; Mathew, Jacob
Abstract: Low-dose interventional x-ray systems have been shown to substantially reduce radiation dose in the pediatric and adult structural and interventional realm. We evaluated our single-center experience with Philips AlluraClarity software for all cardiovascular procedures; we also compared performance relative to patient body size. A total of 1155 patients were included. Data on dose area product (DAP) for radiation exposure, along with body surface area (BSA) and fluoroscopy time, were retrospectively collected for 467 patients before implementation of the Clarity system and for 688 patients after system implementation. DAP was then compared to BSA and fluoroscopy time. BSA was categorized into four quartiles to assess the relationship between radiation dose across small to large patient size populations. The mean BSA between two groups was similar (2.03 vs 2.02 m 2, P  = 0.48), with a 44.7% reduction in radiation dose with DAP indexed to BSA. A significant reduction in radiation dose was seen across all quartiles, with the highest reduction in the post-Clarity sample population with the largest BSA. Fluoroscopy time in the pre-Clarity period was lower than in the post-Clarity period (mean of 7.6 vs 10.2  min; P ≤  0.001), with a total 57.7% radiation dose reduction with DAP indexed to fluoroscopy time ( P ≤  0.001). There was a 45.2% overall decrease in radiation dose with AlluraClarity ( P  ≤ 0.001). In conclusion, AlluraClarity significantly reduced overall radiation dose, irrespective of BSA. The largest reduction in radiation was seen in patients with the highest BSA, suggesting that obese patients derive the most benefit. To our knowledge, this is the first study to describe this relationship with BSA and AlluraClarity. The Clarity system also substantially reduced radiation dose despite longer fluoroscopy time.